1996
DOI: 10.3354/meps143151
|View full text |Cite
|
Sign up to set email alerts
|

Epibenthic community patterns on the continental slope off East Greenland at 75* N

Abstract: ABSTRACT. Megabenthic assemblages on the East Greenland continental slope at 75" N were surveyed at 8 locations between 190 and 2800 m depth using sea floor images taken vertically with a still camera. A total of 91 epibenthic species with 14447 indiv~duals were identified from 422 photographs depicting 297 n12 of the sea floor. Classification and ordination analysis defined 3 fauna1 zones that corresponded to different depth regions of the continental margin: shelf break, upper slope and lower slope. Megafaun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 29 publications
6
54
0
Order By: Relevance
“…As in our study, distribution patterns of species assemblages and richness were best correlated with seafloor characteristics quantified by the presence of hard surfaces (e.g. number of stones) (Haedrich et al 1975, Hecker et al 1980, Hecker 1990a, Mayer & Piepenburg 1996. Recent observations on Browns Bank on the western Scotian Shelf have also shown that dominant benthic epifauna species assemblages are associated with distinct habitat types based primarily on regional geomorphology, sediment texture and water-mass characteristics (Kostylev et al 2001).…”
Section: Gradients In Epifauna Biodiversity Within the Gullymentioning
confidence: 51%
“…As in our study, distribution patterns of species assemblages and richness were best correlated with seafloor characteristics quantified by the presence of hard surfaces (e.g. number of stones) (Haedrich et al 1975, Hecker et al 1980, Hecker 1990a, Mayer & Piepenburg 1996. Recent observations on Browns Bank on the western Scotian Shelf have also shown that dominant benthic epifauna species assemblages are associated with distinct habitat types based primarily on regional geomorphology, sediment texture and water-mass characteristics (Kostylev et al 2001).…”
Section: Gradients In Epifauna Biodiversity Within the Gullymentioning
confidence: 51%
“…By contrast, evenness and species diversity did not differ between channel regions, resembling the macrofaunal community parameters described from the continental margin off Svalbard (Włodarska-Kowalczuk 2004). Overall, benthic community patterns seem to follow a bathymetric/shelf distance zonation at the Greenland Sea slope, which has also been described for megafauna between 190 and 2,800 m depth at 75°N (Mayer and Piepenburg 1996). A seasonally high export of organic particles in the MIZ and increased food availability may sustain high epifaunal densities at the continental rise and the western part of the Ardencaple Canyon (Ramseier et al 1999;Peinert et al 2001).…”
Section: Discussionmentioning
confidence: 96%
“…Seabed imaging techniques such as those used for the description of distribution and community patterns of epibenthic megafauna from soft-bottom environments (e.g. Mayer and Piepenburg 1996;Ambrose et al 2001;Bluhm et al 2005;Soltwedel et al 2009), and biogenic ''substrate islands'' such as sponge stalks (Beaulieu 2001) are valuable tools to quantitatively characterise epibenthic communities on hard substrata (Rice et al 1982;Solan et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A comparison between our findings and those from other regions of the world ocean (Table 5) is only possible if the studies are based on a similar scientific approach, and if geomorphological characteristics as well as the methods are comparable. Our results from the Subantarctic offshore shelf can best be compared with those of Gutt and Starmans (in press) from the high Antarctic Weddell and Lazarev Seas' shelf and two stations of Meyer and Piepenburg (1996) on the northeastern Greenlandic shelf and shelf edge. Despite the extremely varying sampling effort we come to a few general conclusions: In the high Antarctic echinoderms and bryozoans seem to play a more important role in terms of relative abundance at ecologically comparable sampling sites whereas bivalves and sponges were more dominant at the Magellan off-shore stations.…”
Section: Discussionmentioning
confidence: 99%